Strategi Pengelolaan Destinasi Wisata Berkelanjutan di Era Digital - Seno Sumowo; Edi Siswanto; Mushthofa Kamal; Juhanda (SS&H: Studies in Social Sciences and Humanities, 2025)
Digital transformation has become a key factor in the sustainable management of tourist destinations, especially in responding to environmental, social, and economic challenges in the modern tourism era. However, the use of digital technology in destination management still faces various obstacles, such as digital literacy gaps and coordination between stakeholders. This research aims to analyze sustainable tourism destination management strategies in the digital era by emphasizing the role of digital technology and multi-stakeholder collaboration. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews and documentation studies. Data analysis was carried out using digital SWOT analysis to identify internal and external factors, as well as stakeholder mapping to understand the role and relationships between actors in destination management. The results of the study show that digitalization contributes significantly to strengthening sustainable destination branding, increasing tourists' access to information, and forming more responsible visiting behaviors. However, limited digital literacy, uneven technological infrastructure, and the risk of access inequality are still the main challenges in the implementation of digital strategies. The discussion emphasized that digitalization plays a strategic role as a strategic infrastructure in sustainable destination governance and requires inclusive policy support and strong multi-stakeholder collaboration. This research provides theoretical implications by expanding the sustainable tourism framework through the integration of the digital dimension, as well as practical implications for destination managers and policymakers in formulating adaptive sustainable tourism management strategies in the digital age.